Neither sequence variation in the IL-10 gene promoter nor presence of IL-10 protein in the cerebral cortex is associated with Alzheimer's disease. - Culpan, D; Prince, J; Matthews, S; Palmer, L; Hughes, A; Love, S; Kehoe, P; Wilcock, G (2006)
Interleukin 10 (IL-10) is an important anti-inflammatory cytokine produced in response to neuroinflammation and might be involved in modulating the progression of Alzheimer's disease (AD) through inhibiting the action of pro-inflammatory cytokines. We have used immunohistochemistry, Western blotting, real time-PCR (RT-PCR) on frontal (BA 6/24) and temporal (BA 20-22) neocortex and hippocampus from AD and control brains as well as genetic association analysis to address the possible involvement of IL-10 in AD. Expression of IL-10 in AD and control brains at both protein and mRNA levels were detected. However, the level of expression, particularly of IL-10 protein, varied considerably in individual brains and we did not find a significant difference between AD and controls. Using direct sequencing we examined five single nucleotide polymorphisms (SNPs) (-3538, -1354, -1087, -824, -597) and two microsatellites (IL-10-G, IL-10-R) in the promoter region of the IL-10 gene. None of the identified SNPs were found to be associated with AD either individually or as haplotypes. Levels of IL-10 protein and gene expression examined also did not appear to be related to AD. Despite this being a relatively small sample, these data suggest that IL-10 does not play a major role in the development of AD.